GUGATAN PERBUATAN MELAWAN HUKUM PENGADILAN HUBUNGAN INDUSTRIAL BENGKULU (PUTUSAN NOMOR 6/PDT.SUS-PHI.2020/PN BGL) - Hartanto Wibowo; Andari Yurikosari (Fakultas Hukum Universitas Trisakti, 2021)
The Industrial Relations Court is not authorized to examine and decide on other cases but Supreme Court Circular Number 3 of 2018 adds a little bit regarding the instructions that apply within the Supreme Court and below, namely the Industrial Relations Court can examine and decide on lawsuits for unlawful acts. The problems: how is the argument for the lawsuit against the law based on the judge's consideration in deciding the rights dispute between Ufa Fachrulrozy and PT Julang Oca Permana based on statutory regulations and what are the legal consequences for the judgment of the judge who rejects the argument for an unlawful act as an authority in the industrial relations court? This article uses synchronization normative legal, using secondary data and primary data, analyzed qualitatively, and concluded logically deductively. In conclusion, the results of the study show that the panel of judges in Decision Number: 6/Pdt.sus-PHI/2020/PN Bgl is more inclined to use the Law than the Supreme Court Circular Letter and the legal consequence is that the plaintiff is harmed and the plaintiff can submit a legal remedy in the form of cassation.